Chemistry smart phone app with gamification elements for personalised learning - Ng, Jo-Han (2015)
The big challenge in present day education system comes in the form of engaging the Millennials and tackling the issue of their intrinsic motivation. While this can be tackled with personalised learning, which is more effective than conventional method of mass education of students, the associated cost for classroom level deployment is prohibitively expensive on a larg e-sca le basis . Considering that the Millennials have imprecedented ted access to modern portable technology, the presently ubiquitous smart phone/tablet can be the ideal vices for mass deployment of personalised learning. In this study, 80 Millennial generation Form 4, form 5 (whom will be taking the Malaysian Sijil Pelajaran Malaysia (SPM) examination) and post-SPM students, under the Malaysian education system, are exposed to the concept of education gamification through a chemistry smart phone/tablet app, purposed-built with SPM syllabus (O-Level equivalent) in mind. additionally, we surveyed students on their perception towards learning Chemistry , learning needs, spending on additional tuition, access to smart devices, technology saviness and inclination to engage with Chemistry phone apps. From the survey, we found that students are motivated by the game-based personalised learning system for learning chemistry. This has immense potential to democratise personalised learning at national. level. In all, this paper provides evidence of potentially cost-effective personalised learning, which can be considered in future curriculum development for a well-planned education programme, directly addressing adolescent needs.